Identification of Escherichia coli in Patients with Diabetes Mellitus Suspected of Urinary Tract Infection Complications at the Imbanagara Health Center, Ciamis Regency - Ariyadi, Rivana; Ruhimat, Undang; Fathurrohman, Reza (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objectives: Diabetes Mellitus (DM) is a metabolic condition characterized by hyperglycemia due to irregular insulin production and action. Increased levels of glucose in the blood cause people with diabetes mellitus to experience glycosuria and neutrophil dysfunction, causing the risk of being susceptible to infectious diseases. One disease that can cause complications is urinary tract infection. This study aims to determine the presence or absence of Escherichia coli bacteria in the urinary tract of patients with diabetes mellitus suspected of complications of urinary tract infection. Methods: The method used in this study uses a descriptive method, namely the researcher only identifies Escherichia coli in patients with diabetes mellitus suspected of complications of urinary tract infection at the Imbanagara Health Center, Ciamis Regency Results: Based on the results of the research that has been done, it can be concluded that of the 12 samples examined, 5 samples were indicated positive for Escherichia coli bacteria, while 7 other samples found Enterobacter bacteria. Conclusion: Based on the results of the research that has been carried out, it can be concluded that of the 12 samples examined, 5 samples indicated positive for Escherichia coli bacteria, while 7 other samples found Enterobacter bacteria.